Fermented soybean meal (FSFM) and Spirulina (Arthrospira platensis) biomass as potential substitutes for fishmeal for tilapia and other fish species cultivated in intensive systems (Revista de Ciências Agroveterinárias, 2024)
The constant and significant growth of aquaculture activity necessitates the intensification of cultivation systems and develop more efficient,  cost-effective and bioavailable diets. In this context, the use of alternative ingredients to fishmeal, such as fermented soybean meal (FSFM) and Spirulina biomass (Arthrospira platensis), should be considered. This review article aims to conduct a survey of studies with alternative ingredients to fishmeal for tilapia and other fish species, cultivated in more intensive farming systems, such as the biofloc system.Thus, it can be conclude that these ingredients allow the replacement (partial or total) of fishmeal in diets for Nile tilapia and other fish species. Furthermore, important information about the benefits arising from intensive systems, benefits that justify their use in the cultivation of these animals, were also observed.
Keywords: zootechnical performance; animal nutrition; animal health; biofloc system